The Effectiveness Of Classical Guidelines Using Film Media To Improve Student Discipline - Yustika, Dede Teska; Suhendri, Suhendri; Ajie, Rohastono; Paramartha, Wayan Eka (Department of Guidance and Counseling, FIP, Undiksha, 2020)
This research is aimed at increasing students' understanding of discipline through classical guidance services with film media. This study uses quantitative research design using the posttest-only control design. The subjects of this study were students of class XI Pelita Nusantara 2 Vocational School in Semarang collecting 62 students who were divided into two groups namely the experimental group and the control group, collecting subjects using cluster random sampling, data collection techniques used were interviews. The instrument used in the study is the psychological scale of discipline, through a Likert scale design using four options namely strongly agree (SS), agree (S), disagree (TS), very unacceptable (STS) the level of reliability is 0.914. Data analysis techniques used the t_independent sample test (O1-O2).The results of the study showed that there was a significant difference between classical guidance services and media films that were effective in increasing student discipline. This is shown by the results of statistical analysis through the t_independent test of the test sample that is the control group sig.0,000 < 0.05 which shows a significant increase, while the experimental group sig. 0,000 < 0.05 means significant improvement. Thus the classical tutoring service with effective film media increases student discipline.